Influence of Pore Characteristics on the Fate and Distribution of Newly Added Carbon - Quigley, Michelle Y.; Negassa, Wakene C.; Guber, Andrey K.; Rivers, Mark L.; Kravchenko, Alexandra N. (Frontiers in Environmental Science, 2018)
Pores create a transportation network within a soil matrix, which controls the flow of air, water, and movement of microorganisms .The flow of air, water, and movement of microbes, in turn, control soil carbon dynamics. Computed microtomography (μCT) allows for the visualization of pore structure at micron scale, but quantitative information on contribution of pores to fate and protection of soil carbon, essential for modeling, is still lacking. This study uses the natural difference between carbon isotopes of C3 and C4 plants to determine how the presence of pores of different sizes affects spatial distribution patterns of newly added carbon immediately after plant termination and then after one-month incubation. We considered two contrasting soil structure scenarios: soil with the structure kept intact and soil for which the structure was destroyed via sieving. For the experiment, soil was collected from 0-15 cm depth from a 20-year continuous maize (Zea mays L., C4 plant) experiment into which cereal rye (Secale cereale L., C3 plant) was planted. Intact soil fragments (5-6 mm) were procured after 3 months rye growth in a greenhouse. Pore characteristics of the fragments were determined through μCT imaging. Each fragment was sectioned and total carbon, total nitrogen, δ13C, and δ15N were measured. The results indicate that, prior to incubation, greater presence of 40-90 μm pores was associated with higher levels of C3 carbon, pointing to the positive role of these pores in transport of new C inputs. Nevertheless, after incubation, the association became negative, indicating greater losses of newly added C in such pores. These trends were statistically significant in destroyed-structure soil and numerical in intact-structure soil. In soils of intact-structures, after incubation, higher levels of total carbon were associated with greater abundance of 6.5-15 and 15-40 μm pores, indicating a lower carbon loss associated with these pores. The results indicate that, in the studied soil, pores of 40-90 μm size range are associated with the fast influx of new C followed by its quick decomposition, while pores <40 μm tend to be associated with C protection.